Shape-Dependent Radiosensitization Effect of Gold Nanostructures in Cancer Radiotherapy: Comparison of Gold Nanoparticles, Nanospikes, and Nanorods - Ma, Ningning; Wu, Fu-Gen; Zhang, Xiaodong; Jiang, Yao-Wen; Jia, Hao-Ran; Wang, Hong-Yin; Li, Yan-Hong; Liu, Peidang; Gu, Ning; Chen, Zhan (ACS applied materials & interfaces, 2017)
The shape effect of gold (Au) nanomaterials on the efficiency of cancer radiotherapy has not been fully elucidated. To address this issue, Au nanomaterials with different shapes but similar average size (∼50 nm) including spherical gold nanoparticles (GNPs), gold nanospikes (GNSs), and gold nanorods (GNRs) were synthesized and functionalized with poly(ethylene glycol) (PEG) molecules. Although all of these Au nanostructures were coated with the same PEG molecules, their cellular uptake behavior differed significantly. The GNPs showed the highest cellular responses as compared to the GNSs and the GNRs (based on the same gold mass) after incubation with KB cancer cells for 24 h. The cellular uptake in cells increased in the order of GNPs > GNSs > GNRs. Our comparative studies indicated that all of these PEGylated Au nanostructures could induce enhanced cancer cell-killing rates more or less upon X-ray irradiation. The sensitization enhancement ratios (SERs) calculated by a multitarget single-hit model were 1.62, 1.37, and 1.21 corresponding to the treatments of GNPs, GNSs, and GNRs, respectively, demonstrating that the GNPs showed a higher anticancer efficiency than both GNSs and GNRs upon X-ray irradiation. Almost the same values were obtained by dividing the SERs of the three types of Au nanomaterials by their corresponding cellular uptake amounts, indicating that the higher SER of GNPs was due to their much higher cellular uptake efficiency. The above results indicated that the radiation enhancement effects were determined by the amount of the internalized gold atoms. Therefore, to achieve a strong radiosensitization effect in cancer radiotherapy, it is necessary to use Au-based nanomaterials with a high cellular internalization. Further studies on the radiosensitization mechanisms demonstrated that ROS generation and cell cycle redistribution induced by Au nanostructures played essential roles in enhancing radiosensitization. Taken together, our results indicated that the shape of Au-based nanomaterials had a significant influence on cancer radiotherapy. The present work may provide important guidance for the design and use of Au nanostructures in cancer radiotherapy.